Radicular pain caused by Schmorl's node: a case report - Kim,Saeyoung (2018)
Abstract Schmorl's node a focal herniation of intervertebral disc through the end plate into the vertebral body. Most of the established Schmorl's nodes are quiescent. However, disc herniation into the vertebral marrow can cause low back pain by irritating a nociceptive system. Schmorl's node induced radicular pain is a very rare condition. Some cases of Schmorl's node which generated low back pain or radicular pain were treated by surgical methods. In this article, authors reported a rare case of a patient with radicular pain cause by Schmorl's node located at the inferior surface of the 5th lumbar spine. The radicular pain was alleviated by serial 5th lumbar transforaminal epidural blocks. Transforaminal epidural block is suggested as first conservative option to treat radicular pain due to herniation of intervertebral disc. Therefore, non-surgical treatment such as transforaminal epidural block can be considered a first treatment option for radicular pain caused by Schmorl's node.